NIRS : Network intrusion detection and active-response system : group report - Adedayo Adetoye; Andy Choi; Marina Md. Arshad; Olufemi Soretire (London : University College London, 2003)
Thesis (Sarjana Sains (Sains Komputer) - University College London, 2003